Comparative evaluation of laparoscopic splenectomy versus open splenectomy - H. I. Okhrimenko; M. H. Holovko; V. A. Hrushka; Ye. I. Haidarzhi; O. O. Pоdluzhnyi (Zaporožskij Medicinskij Žurnal)
The aim of research: to study the short-term treatment results in patients with blood diseases, portal hypertension, pathology of the spleen who underwent laparoscopic splenectomy based on the surgical indications in comparison with the treatment results in the patients who underwent open surgery.